(untitled) (La U Investiga, 2023)
Pressure in pregnancy is a highly prevalent pathology worldwide, however this pathology has not been given due importance, knowing that it has consequences for both the mother and the fetus. The objective of this article is to determine the frequency of depression and risk factors in pregnant women attended in Ibarra Health Centers.A quantitative, observational, and correlational cross-sectional study was carried out, the sample consisted of 120 pregnant women included through non-probabilistic sampling. For data collection, a questionnaire was used that contained psychosocial, clinical, and sociodemographic data, the Edinburgh Perinatal Depression Scale, and the family APGAR Scale. The results obtained are that the population studied has a high prevalence of depression in pregnancy with a percentage of 35%, which represents a frequency of 42 positive cases of 120 pregnant women studied. Among the socioeconomic factors studied as a possible risk factor for developing depression during pregnancy, we find pregnant women over 35 years of age, low schooling, living in a rural population, unstable employment and unemployment. Regarding the clinical characteristics as possible risk factors, multiparity, history of abortion and complications in the current pregnancy are presented. In relation to psychosocial factors as possible risk factors, the consumption of psychoactive substances, a history of depression, not having social or family support, moderate and severe family dysfunction, and domestic violence are evident.